Transverse mode revival of a light-compensated quantum memory - Yang, Fan; Mandel, Torsten; Lutz, Christian; Yuan, Zhen-Sheng; Pan, Jian-Wei (Physical review. A, Atomic, molecular, and optical physics, 2011)
A long-lived quantum memory was developed based on light-compensated cold 87Rb atoms in a dipole trap. The lifetime of the quantum memory was improved by 40 folds, from 0.67 to 28 ms with the help of a compensation laser beam. Oscillations of the memory efficiency due to the transverse mode breathing of the singly excited spin wave have been clearly observed and clarified with a Monte Carlo simulation procedure. With detailed analysis of the decoherence processes of the spin wave in cold atomic ensembles, this experiment provides a benchmark for the further development of high-quality quantum memories.